LEGAL REVIEW OF RECORDING CHANGES IN MARITAL STATUS WITHOUT AN AUTHENTIC DEED - Suhaif (Jurnal Al Tasyri'iyyah, 2024)
ABSTRACT The purpose of this research is to reveal the legal review of recording changes in marital status without an authentic deed. This research is qualitative research, the type of research is library research. The data collection method used is literature study. The results showed that; Of the several forms of recording changes in marital status, there are 2 (two) types of recording marital status without a valid legal basis (authentic deed), namely “unrecorded marriage” and “unrecorded divorce”. Legally formal changes in marital status should use a legal basis in the form of an authentic deed. Sirri marriages that occur are considered to fulfill the pillars and conditions, only they do not have time to be registered at the KUA and take place without the supervision of a Marriage Registration Officer. The marriage is validated by the Religious Court because it is in line with shari'a and the Marriage Law or Regulation. Keywords: Legal Review; Recording Changes in Marital Status; Authentic Deed.